The Relationship Between Several Physical Properties of Soil to Soil Aggregate Stability Due to Distance in Acid Sulfate Histosol Soils in Oil Palm Plantations at Serdang Jaya Village - Nasution, Hasriati; Yusfaneti, Yusfaneti; Saad, Asmadi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The objective of this study is to examine the relationship between soil properties and aggregate stability in oil palm plantations, influenced by varying distances from the Betara River. Soil analysis was conducted at the Soil Physics and Chemistry Laboratory, Faculty of Agriculture, Jambi University. Soil samples were collected using the Proportional Random Sampling method across plantation areas located at distances of 50 m, 500 m, 1000 m, and 1500 m from the river. The parameters observed included soil organic carbon content, soil moisture content, bulk density, total pore space, percentage of soil aggregates, and aggregate stability. Each treatment was replicated 15 times. To determine the physical properties of the soil and their relationship with river proximity, an independent sample t-test at a 5% significance level was used, followed by multiple linear regression analysis (Steel and Torrie, 1995). The results showed that the distances of 50 m and 500 m had similar values for organic matter content, bulk density, total pore space, moisture content, permeability, aggregate percentage, and aggregate stability. However, these values differed significantly from those observed at distances of 1000 m and 1500 m. Furthermore, multiple linear regression analysis revealed that organic carbon content and soil moisture were the dominant factors influencing aggregate stability, with a correlation coefficient (R) of 0.77. This study provides empirical evidence on how river proximity affects soil physical properties and aggregate stability in oil palm plantations. It highlights the importance of soil organic carbon and moisture content as key determinants of aggregate stability, offering valuable insights for land management strategies in riparian agricultural areas.